PSYCHOLOGICAL CAPITAL IMPACT ON EXTRA ROLE BEHAVIOUR VIA WORK ENGAGEMENT: EVIDENCE FROM THE PAKISTANI BANKING SECTOR (International Journal of Banking and Finance, 2021)
The banking sector in Pakistan has always been one of the most significant economic sectors of the country. The purpose of this paper has been to identify the factors urging bank employees to volunteer themselves for activities outside of their formal job obligations. A total of 315 responses were gathered from the employees of the four private commercial banks in Pakistan. The researchers tested the relationship between the four facets of psychological capital (i.e., efficacy, resilience, optimism, and hope) and the two dimensions of extra role behaviour (individual and organisational). The researchers used the SPSS version 23 to analyse the demographic profiles of the respondents, and the SmartPLS version 3 to test the hypotheses formed using the structural equation modelling technique. The researchers also investigated the mechanism through which psychological impacts extra role behaviour. Under the Job Demands-Resources (JDR) model, work engagement is employed as a mediating variable. The results of the study revealed a significant positive relationship between efficacy, optimism, and resilience with extra role behaviours. However, hope remained insignificant to extra role behaviours. The study outcomes also supported the major hypotheses on the mediating role of work engagement in the relationship between the psychological capital and extra role behaviour. Recommendations for future studies and the limitations of the present study were aslo discussed.